Separation of m/p-Aminoacetophenone Using Hydrotropy. Issue 4 (2012) - Dhinakaran, M.; Morais, Antony Bertie; Gandhi, N. Nagendra
Abstract : The aqueous solubilities of m/p-aminoacetophenone in different concentrations (0-3.0 mol/L) of hydrotropes such as diethyl nicotinamide, sodium pseudocumene sulfonate and sodium thiocyanate solutions at different system temperatures (303K to 333K) were studied. The percentage extraction (%E) of m- aminoacetophenone from m/p-aminoacetophenone mixture increases with increase in hydrotrope concentration. A Minimum Hydrotrope Concentration (MHC) in the aqueous phase was required to initiate the significance of the %E of m-aminoacetophenone. Percentage extraction (%E) is the ratio of moles of m-aminoacetophenone extracted in presence and absence of a hydrotrope. The sensitivity and feasibility of the proposed process are examined by carrying out solubilization and equilibrium precipitation experiments with the mixtures of various compositions. The effectiveness of hydrotropes was measured in terms of Setschenow constant Ks. The extraction data are also fitted in a polynomial equation as the function of hydrotrope concentration. The solubilized material can be recovered by dilution with water.